Strategic Human Resource Management: An Analysis of Career Abandonment for Healthcare Technicians in the Provision of Care at Nampula Central Hospital (HCN) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study aimed to understand the factors that contributed to the abandonment of the health technician career at the Nampula Central Hospital. The research adopted a quantitative, descriptive approach, using bibliographic and case study procedures. The universe consisted of 188 employees who abandoned their health technician career, from which a sample of 30 participants was extracted, selected through non-probabilistic convenience sampling. The results show that abandonment occurred mainly in areas considered strategic by the Ministry of Health, namely Pharmacy Technician, General Medicine Technician, Maternal and Child Health Nursing Technician, General Nursing Technician, and Anesthesia Technician, representing 96.70% of the cases analyzed. Occupational stress was found to be one of the main factors associated with abandonment, and 26.6% of participants reported being under pressure due to excessive tasks and shift work. It was also observed that 50% of respondents stated that the decision to abandon their career was not related to financial factors, but to a loss of professional interest and a desire to face new challenges. On the other hand, 46.67% indicated the search for better salary conditions as the main motivation, while 3.33% stated that they no longer identified with the technical training they had obtained.Abandoning a career as a health technician stems from a combination of organizational, motivational, and economic factors, requiring institutional strategies aimed at professional development, improving working conditions, and strengthening motivation in the hospital context.